High Risk of Readmission in Octogenarians Undergoing Primary Hip Arthroplasty. Issue 12 (December 2017) - Malkani, Arthur L.; Dilworth, Brian; Ong, Kevin; Baykal, Doruk; Lau, Edmund; Mackin, Theresa N.; Lee, Gwo‐Chin
Abstract : Background : As life expectancy increases, more elderly patients with end‐stage hip arthritis are electing to undergo primary THA. Octogenarians undergoing THA have more comorbidities than younger patients, but this is not reflected in risk adjustment models for bundled care programs. The burden of care associated with THA in octogenarians has not been well characterized, and doing so may help these value‐based programs make adjustments so that this vulnerable patient population does not risk losing access under accountable care models. Questions/purposes : The purpose of this study was to describe care use, comorbidities, and complications among octogenarians undergoing primary THA. Methods : Five percent of the Medicare national administrative claims data was queried to identify patients diagnosed with hip osteoarthritis between January 1, 1998, and December 31, 2013. Patients who underwent primary THA were identified and followed longitudinally during the study period using their unique, encrypted Medicare beneficiary identifiers. We compared risk factors and complications between the octogenarian group versus those aged 65 to 69 years. Multivariate Cox regression was used to evaluate the effect of patient/hospital factors on risk of revision, periprosthetic joint infection, dislocation, venous thromboembolism (VTE), and mortality. Patient factors in the model included age, sex, race, region, socioeconomic status, and health status based on Charlson comorbidity score 12 months before replacement surgery. Results : There were 11, 960 THAs in the octogenarians in 1998, which increased to 21, 620 in 2013, an 81% increase during this study period. Octogenarians were more likely to have a Charlson score of 3 or higher than those patients aged 65 to 69 years (30% versus 17%, odds ratio [OR] 2.07 [1.98‐2.20]; p < 0.001), and they were more likely to have coronary artery disease or congestive heart failure (47% versus 29%, OR 2.16 [2.06‐2.26]; p < 0.001). The octogenarian group had a greater risk of dislocation (+12%, p = 0.01), VTE (+14%, p < 0.001), and mortality (+150%, p < 0.001) compared with the younger age cohort. A total of 21% of the octogenarians were readmitted after surgery compared with 12% for patients in the younger group (OR=1.64, 95% confidence interval 1.54‐1.75; p < 0.001). Conclusions : Because octogenarians are at increased risk of dislocation, VTE, medical complications, and mortality after THA, value‐based care models that penalize hospitals for readmissions and complications may inadvertently result in loss of access to care for this group of patients as a result of the financial makeup of these bundled care models. Value‐based care models were developed to improve care and decrease healthcare costs but may have unintended consequences in the octogenarian with higher complication and readmission risks. Financial losses may lead to institutions from withdrawing from the Bundled Payments for Care Improvement program. To try to prevent this from happening to this vulnerable patient population, bundled care programs should evolve and be modified to allow for risk stratification in the overall payment formula to account for increased age and comorbid conditions to ensure continued successful participation in the program among all the stakeholders. Level of Evidence : Level III, therapeutic study.